EVALUATION OF EMBRYO TOXICITY OF CROCUS SATIVUS (SAFFRON) IN SPRAGUE DAWLEY RATS - RAMESH EDAMULA; M.DEECARAMAN; M.VIJAYALAKSHMI; KRISHNAPPA.H (International Journal of Pharma and Bio Sciences, 2016)
Wistar and Sprague Dawley rats are 2 different rat strains used widely for toxicity study for evaluation of safety of new chemical entity/food additive/generic drugs in various areas like toxicology, pharmacology and mutagenicity assay. However it is evident that genetic variation and differences in the biotransformation enzymes controlled by genes have been well documented among strains resulting in differences in sensitivity to chemicals. Crocus sativus (saffron) widely used as a food additive and as active components in many traditional medicine and modern pharmacology has been found to be quite safe without any evidence of maternal and embryo toxicity in Wistar strain rats up to the highest dose of 1000 mg/kg bodyweight. Hence the present study was aimed to evaluate if any differences are observed when using Sprague Dawley strain of rats. In the present investigation results indicated that saffron was safe in pregnant Sprague Dawley strain of rats to the dose level of 1000 mg/kg body weight without any maternal and embryo toxicity. Thus the results indicated that there were no strain differences between pregnant Wistar and Sprague Dawley strain of rats in the response to the exposure of saffron administered orally.